2013
DOI: 10.1021/ja4032874
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum–Ligand Cooperative N–H Bond Activation and an Example of Dehydrogenative Coupling

Abstract: Activation of N-H bonds by a molecular aluminum complex via metal-ligand cooperation is described. ((Ph)I2P(2-))AlH (1b), in which (Ph)I2P(2-) is a tridentate bis(imino)pyridine ligand, reacts with anilines to give the N-H-activated products ((Ph)HI2P(-))AlH(NHAr) (2). When heated, 2 releases H2 and affords ((Ph)I2P(-))Al(NHAr) (3). Complex 1b catalyzes the dehydrogenative coupling of benzylamine to afford H2, NH3, and N-(phenylmethylene)benzenemethanamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 31 publications
3
98
0
1
Order By: Relevance
“…We have previously reported that aluminum complexes of Ph I 2 P are able to adopt both symmetric and asymmetric electronic structures upon two-electron reduction and this result was observed crystallographically. 9,33 However, in that previous instance with asymmetric complexes of Al(III), the 1 H-NMR spectra displayed only an average signal that could have been consistent with the symmetric electronic structure of Ph I 2 P (B Chart 1).…”
Section: Synthesis Of Complexesmentioning
confidence: 74%
“…We have previously reported that aluminum complexes of Ph I 2 P are able to adopt both symmetric and asymmetric electronic structures upon two-electron reduction and this result was observed crystallographically. 9,33 However, in that previous instance with asymmetric complexes of Al(III), the 1 H-NMR spectra displayed only an average signal that could have been consistent with the symmetric electronic structure of Ph I 2 P (B Chart 1).…”
Section: Synthesis Of Complexesmentioning
confidence: 74%
“…Complexes with general formulation ( Ph I 2 P n− )AlX 2 were isolated in two oxidation states, where n =1, 2 24. The most notable feature of the electronic structure of complexes of the two‐electron reduced tridentate I 2 P ligand, ( Ph I 2 P 2− )AlX, is the ability of the 2− oxidation state to support multiple resonance forms of I 2 P. The most commonly observed resonance form is asymmetric with reduction localized at the pyridyl and one of the imino donor ligands (Scheme ).…”
Section: Reduced‐ligand Complexes Of Aluminummentioning
confidence: 99%
“…12 We have previously reported that ( Ph I 2 P 2− )AlH (1; Ph I 2 P = 2,6-(2,6-i Pr 2 -C 6 H 3 NCPh) 2 C 5 H 3 N) activated the N−H bonds in anilines and benzylamine. 4 We now report the synthesis of [( Ph HI 2 …”
Section: T He Addition Of O−h Bonds Across the Metal−ligand Bondsmentioning
confidence: 99%